Wall stress enhanced exocytosis of extracellular vesicles as a possible mechanism of left-right symmetry-breaking in vertebrate development. (7th January 2019) - Solowiej-Wedderburn, J.; Smith, D.J.; Lopes, S.S.; Montenegro-Johnson, T.D.
Highlights: A model of the wall stresses induced by nodal cilia is derived. Applying typical parameters, these stresses are between 0.2 to one Pa. These values are comparable to experiments showing fluid shear-enhanced exocytosis. Abstract: In certain vertebrate species, the developing embryo breaks left-right symmetry in a transient organising structure: the "Left-Right Organiser" (LRO) known as the "node" in mice, and "Kupffer's vesicle" in fish. Directional cilia-driven flow is integral to this symmetry-breaking process, however the mechanism by which this flow is translated into an asymmetric signal remains contested; the principal theories are either flow transport of vesicles containing morphogens, or flow mechanosensing by cilia. Whilst some recent work favours the morphogen theory, other findings seem to support mechanosensing. In this study, we consider a hypothesis whereby the cilia themselves drive the release of morphogen-carrying extracellular vesicles (EVs) into the LRO; namely, that fluid stresses on the cell membrane induce/enhance exocytosis of EVs. Using a mathematical model, we calculate significant wall normal and shear stresses for a range of typical cilium parameter values comparable to levels capable of enhancing exocytosis. This mechanism may be able to reconcile the apparently conflicting experimental evidence.